Prevalence and Predictors of Poly-Victimization of Adolescents in England and Wales - Tura, Ferhat (Journal of interpersonal violence, 2023)
This study examined the change in the prevalence of adolescent poly-victimization and individual and area predictors of poly-victimization in England and Wales. The national representative longitudinal Offending, Crime and Justice Survey (2003–2006) was analyzed with data from 2,066 adolescents, aged between 10 and 18 years (mean ± SD at Time 1 = 13.08 ± 2.01), using multilevel multinomial logit models. Findings revealed that the majority of the adolescents (41.6%, 48.5%, 54.6%, 61.6%, respectively) did not experience victimization between 2003 and 2006. However, 28.3%, 25.9%, 19.5%, and 14.5% of the adolescents experienced poly-victimization (experiencing more than or equal to two types of victimizations), with a decrease of 13.8% over the 4-year period. Furthermore, some adolescents were consistent poly-victims, meaning they were poly-victims in all years that they participated in the survey. In particular, 3.57% of the adolescents who participated in the four waves of the survey were poly-victims in all years; 7.41% of the adolescents who participated in three of the four waves of the survey were poly-victims in all years; and 25.79% of the adolescents who participated in two of the four waves of the survey were poly-victims in both years. Statistically significant predictors of poly-victimization included having parents who have been in trouble with the police, offending, participating in community-related activities, being a boy, not managing income well, and living in an urban or deprived area. Offending had the greatest impact on poly-victimization. Findings highlight that adolescent poly-victimization in England and Wales decreased between 2003 and 2006 but some adolescents were more likely to experience poly-victimization due to individual, familial, and area characteristics. The findings therefore indicate that a holistic approach is needed to reduce adolescent poly-victimization and suggest that targeting area deprivation should be the priority.